Joining Together to Build More: The New England Software Carpentry Library Consortium - Thea P. Atwood; Andrew T. Creamer; Joshua Dull; Julie Goldman; Kristin Lee; Lora C. Leligdon; Sarah K. Oelker (Journal of eScience Librarianship, 2019)
In 2017 a group of academic library and information technology staff from institutions across New England piloted a process of joining The Carpentries, an organization developed to train researchers in essential computing skills and practices for automating and improving their handling of data, as a consortium. The New England Software Carpentry Library Consortium (NESCLiC) shared a gold-level tier membership to become a Carpentries member organization. NESCLiC members attended a Software Carpentry workshop together and then participated in instructor training as a cohort, collaborating on learning the material, practicing, and beginning to host and teach workshops as a group. This article describes both the successes and challenges of forming this new consortium, suggests good practices for those who might wish to form similar collaborations, and discusses the future of this program and other efforts to help researchers improve their computing and data handling skills.